(untitled) (Research, Society and Development, 2020)
Programmed obsolescence is the application of techniques to a product, in order to artificially limit its useful life, making the repetitive purchase of an updated model mandatory. Our goal is to analyze how Environmental Education can assist in a balanced relationship between consumption and environmental preservation. Our work is a narrative review and we use the deductive approach method, complemented by bibliographic analysis, with essential elements for understanding and characterizing the theme. We note that programmed obsolescence is a practice that is aggressive to nature and society. Therefore, in order to minimize the effects of unbridled production of superfluous goods and to seek the possibility for a more sustainable society, we observed that a behavioral change in the consumer is necessary. And for that, Environmental Education is fundamental, as a starting point for an understanding between consumption patterns and the guarantee of an ecologically balanced environment for present and future generations.